Interactive Science Textbook Integrated with Quranic Values: Buku Teks Sains Interaktif yang Terintegrasi dengan Nilai-Nilai Al-Quran - Zahroh, Nihlatus; Nisak, Nur Maslikhatun (Indonesian Journal of Education Methods Development, 2025)
General background: The integration of science education with spiritual values is increasingly recognized as essential in providing holistic learning experiences for students. Specific background: In Islamic education, embedding Al-Qur’an values within Natural Science learning can foster both cognitive understanding and spiritual growth. Knowledge gap: However, few learning resources explicitly combine Natural Science materials with Quranic references in a creative and engaging format for elementary-level learners. Aims: This study introduces an Interactive Natural Science Textbook designed to merge scientific concepts with relevant Quranic verses. Results: The textbook consists of 20 creatively structured pages covering plant parts and photosynthesis, accompanied by verses from the Al-Qur’an, and is shown to attract students’ reading interest while deepening their scientific and religious knowledge. Novelty: Unlike conventional science textbooks, this resource integrates multimedia elements and Quranic context, offering a balanced approach between academic learning and faith development. Implications: This textbook contributes to strengthening elementary Islamic education by p Highlights: Combines Natural Science with Quranic verses. Designed for elementary Islamic education. Promotes holistic learning: academic and spiritual. Keywords: Interactive Textbook, Natural Science, Quranic Values, Islamic Education, Elementary Learning